Medical Qigong for Mobility and Balance Self-Confidence in Older Adults - Stahl, James E.; Belisle, Shoshana S.; Zhao, Wenyan (Frontiers in Medicine, 2020)
Background/Objectives: Physical inactivity, sedentary lifestyle, and impaired neuromuscular function increases fall risk and fractures in our aging population. Mind-body modalities, improve strength, balance and coordination, mitigating these risks. This study examined whether a manualized Medical Qigong protocol measurably improves balance, gait, and health self-confidence among older adults. Design: Randomized prospective cohort pre-post study with wait time control. Setting: Two martial arts centers in Massachusetts and Arizona. Participants: Ninety-five adults age ≥ 50 (mean age 68.6 y.o., range 51–96) were randomly assigned to an immediate start group (N = 53) or 4-week delayed start group (N = 43). Intervention: A 10 form qigong protocol taught over 12 weekly classes. Measurments: Primary outcome measures were the Community Balance and Mobility Scale (CBMS) and Activities-Specific Balance Confidence (ABC) Scale. Data was collected at baseline, 1-month and 4-months. Results: Both groups at both sites demonstrated improved balance and gait (CBMS + 11.9 points, p < 0.001). This effect was strongest in patients in their 60 s (CBMS +12.9 p < 0.01) and 70 s (CBMS + 14.3, p < 0.001), was equal across genders and socioeconomic status. Balance self-confidence did not significantly change (ABC + 0.9, p = 0.48), though several elements within ABC trended toward improvement [e.g., walk up/down ramp (p = 0.07), bend over/pick up (p = 0.09)]. Falls in the past year was inversely correlated with balance self-confidence (p = 0.01). Conclusion: A 12-week manualized Medical Qigong protocol significantly improved balance and gait and modestly improved balance self-confidence among older adults. Medical Qigong may be a useful clinical intervention for older adults at heightened risk for falls and related injuries. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04430751.